HUBUNGAN KECEMASAN ORANG TUA DENGAN DEPRESI PADA ANAK SEKOLAH DASAR DI SDN 03 SIMPANG HARU PADANG - Wuri Komalasari (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Mental health is important in the development of children, because children are thenext generation for the future. One of the mental health problems in children is depression.Depression is a mental disorder characterized by the appearance of symptoms ofdecreased mood, loss of interest in something, feelings of guilt, sleep disturbances, anddecreased of concentration. Depression that occurs in children is caused by two factors:physical and psychological factors. Anxiety are part of the psychological factors that causedepression. The purpose of this study is tosee the relationship of parents anxiety towarddepression in child at SDN 03 Simpang Haru Padang. The type of research used isanalytic with design cross sectional. The sample in this study were 54 people withpurposive sampling technique and research instrument using the Center ForEpidemiological Studies Depression Scale For Children (CES-DC) questionnaireconsisted of 20 statements and the Spance Children Anxiety Scale (SCAS) questionnaireconsisted of 18 statements. The study was conducted in June 2018. From the results of thestudy, found that 46.3% respondents with depression and 46.3% of respondents withanxiety. The result of statistical test shows that there is a significant correlation betweenanxiety with depression in primary school children with P Value = 0.001. It is expectedthat the school, especially at SDN 03 Simpang Haru Padang to further increase efforts toprevent depression in children by increasing the role of counseling teacher at School.Keywords : Depression, Anxiety, School Children